2021
DOI: 10.1002/essoar.10507260.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surface salinity under transitioning ice cover in the Canada Basin: Climate model biases linked to vertical 2 distribution of freshwater

Abstract: The models distribute fresh water over an unrealistically large depth range in recent years, which contributes to the surface salinity bias.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…These findings are consistent with Rosenblum, Fajber, et al. (2021), who show that the model bias can be partly attributed to unrealistic vertical mixing rather than sea ice melt. It appears that the two opposing effects of increased ice melt with warming and surface mixing by faster moving sea ice (and increased surface stress) lead to a more stable stratification in the real world (Peralta‐Ferriz & Woodgate, 2015) and a less stable stratification in the CESM1‐LE in May.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with Rosenblum, Fajber, et al. (2021), who show that the model bias can be partly attributed to unrealistic vertical mixing rather than sea ice melt. It appears that the two opposing effects of increased ice melt with warming and surface mixing by faster moving sea ice (and increased surface stress) lead to a more stable stratification in the real world (Peralta‐Ferriz & Woodgate, 2015) and a less stable stratification in the CESM1‐LE in May.…”
Section: Resultssupporting
confidence: 92%
“…While we find that CESM1‐LE does simulate increases in both sea ice melt and surface stress (Figure 8), the model instead simulates a deepening in the mixed layer. This points to a problem in vertical mixing in the CESM1‐LE, consistent with previous studies (Holloway et al., 2007; Ilıcak et al., 2016; Rosenblum, Fajber, et al., 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rosenblum et al. (2021) found that some coupled models tend to simulate an unrealistic vertical mixing in the upper Arctic Ocean and accordingly fail to capture the observed freshwater change in recent years.…”
Section: Resultsmentioning
confidence: 99%